2011
DOI: 10.1504/ijceell.2011.040198
|View full text |Cite
|
Sign up to set email alerts
|

Using latent semantic analysis to grade brief summaries: some proposals

Abstract: In this paper, we present several proposals in order to improve the LSA tools to evaluate brief summaries (less than 50 words) of narrative and expository texts. First, we analyse the quality of six different methods assessing essays that have been widely employed before (Foltz et al., 2000). The second objective is to analyse how new algorithms inspired by some authors (Denhière et al., 2007) that try to emulate human behaviour to improve the reliability of LSA with human graders when assessing short summarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…The units may be words, phrases, clauses, sentences, paragraphs (Foltz, 1996;Landauer, 1998;Landauer & Dumais, 1997;Landauer, Foltz, & Laham, 1998), or summaries (Foltz, 1996;E. Kintsch et al, 2000;Olmos, León, Escudero, & Jorge-Botana, 2011;Olmos, León, Jorge-Botana, & Escudero, 2009. LSA uses the geometric cosine between two vectors to compute the conceptual similarity between any two units of the text.…”
Section: Computerized Summary Scoring: Natural Language Processingmentioning
confidence: 99%
See 4 more Smart Citations
“…The units may be words, phrases, clauses, sentences, paragraphs (Foltz, 1996;Landauer, 1998;Landauer & Dumais, 1997;Landauer, Foltz, & Laham, 1998), or summaries (Foltz, 1996;E. Kintsch et al, 2000;Olmos, León, Escudero, & Jorge-Botana, 2011;Olmos, León, Jorge-Botana, & Escudero, 2009. LSA uses the geometric cosine between two vectors to compute the conceptual similarity between any two units of the text.…”
Section: Computerized Summary Scoring: Natural Language Processingmentioning
confidence: 99%
“…Empirical evidence has shown that LSA robustly predicts the semantic quality of summaries as perceived by humans (Jorge-Botana, Luzón, Gómez-Veiga, & Martín-Cordero, 2015;E. Kintsch et al, 2000;Olmos et al, 2011Olmos et al, , 2013Sung, Liao, Chang, Chen, & Chang, 2016;Wade-Stein & Kintsch, 2004). One successful system that uses LSA to automatically assess summaries is Summary Street® (E. Kintsch et al, 2000;Wade-Stein & Kintsch, 2004).…”
Section: Computerized Summary Scoring: Natural Language Processingmentioning
confidence: 99%
See 3 more Smart Citations